Role of Institut Hospitalo-Universitaire Méditerranée Infection in the surveillance of resistance to antibiotics and training of students in the Mediterranean basin and in African countries - Peyclit, L. (New Microbes New Infect, 2018)
Surveillance of antibiotic resistance has become a public global concern after the rapid worldwide dissemination of several antibiotic resistance genes. Here we report the role of the Institut Hospitalo-Universitaire Méditerranée Infection created in 2011 in the identification and description of multidrug-resistant bacteria thanks to collaborations and training of students from the Mediterranean basin and from African countries. Since the creation of the institute, 95 students and researchers have come from 19 different countries from these areas to characterize 6359 bacterial isolates from 7280 samples from humans (64%), animals (28%) and the environment (8%). Most bacterial isolates studied were Gram-negative bacteria (n = 5588; 87.9%), mostly from Algeria (n = 4190), Lebanon (n = 946), Greece (n = 610), Saudi Arabia (n = 299) and Senegal (n = 278). Antibiotic resistance was diversified with the detection and characterization of extended-spectrum β-lactamases, carbapenemases and resistance to colistin, vancomycin and methicillin. All those studies led to 97 indexed international scientific papers. Over the last 6 years, our institute has created a huge network of collaborations by training students that plays a major role in the surveillance of resistance to antibiotics in these countries.